THE STATE OF BODY THERMOREGULATION OF DRIVERS OF PASSENGER VEHICLES WHEN WORKING IN DIFFERENT SEASONS OF THE YEAR - B.KH. NUSHERVONI; A.B. BABAEV (Avicenna Tajik State Medical University, 2019)
Objective: To evaluate the state of body thermoregulation of drivers of passenger vehicles when working in different seasons of the year. Methods: 113 drivers of AKIA (Turkey), ISUZU (Japan), LiAZ buses and TIU trolleybuses (Russia) participated in the study. Studies were carried out on the processes of body thermoregulation of drivers of passenger vehicles when working in different seasons of the year in the work shift dynamics in the city of Dushanbe. Results: It has been established that when the temperature of the outdoor air rises, there is a parallel increase in temperature in the cabin buses and trolleybuses, which leads to an increase in body temperature and average weighted skin temperature, to significant moisture loss, and also discomfort body sensation. It should be noted that when working in the warm period of the year with the increase in air temperature in the workplace, the drivers of buses AKIA, ISUZU and LiAZ observed a gradual decline in the shift of systolic pressure from an average of 116.0±2.3 to 112.8±2.2; from 120.3±3.0 to 111.8±2.93, and from 118.6±3.8 to 108.0±3.4 mm Hg, respectively, compared to the baseline levels. Conclusion: Thus, drivers of passenger vehicles perform stressful work in uncomfortable microclimatic conditions, especially when working during the warm period of the year, which causes significant tensions of thermoregulatory processes of their body.